2016
DOI: 10.1021/jacs.6b06361
|View full text |Cite
|
Sign up to set email alerts
|

Facile Incorporation of Pd(PPh3)2Hal Substituents into Polymethines, Merocyanines, and Perylene Diimides as a Means of Suppressing Intermolecular Interactions

Abstract: Compounds with polarizable π systems that are susceptible to attack with nucleophiles at C-Hal (Hal = Cl, Br) bonds react with Pd(PPh3)4 to yield net oxidative addition. X-ray structures show that the resulting Pd(PPh3)2Hal groups greatly reduce intermolecular π-π interactions. The Pd-functionalized dyes generally exhibit solution-like absorption spectra in films, whereas their Hal analogues exhibit features attributable to aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…1.5°. Although the molecular geometry and, therefore, molecular packing in bay-2Pt-PDI is quite different to that in its previously reported Pd analogue, 84 due to the presence of cis-Pt(PPh 3 ) 2 Br rather than trans-Pd(PPh 3 ) 2 Br groups, there is no PDI−PDI π-stacking in either structure.…”
Section: ■ Expermental Methodscontrasting
confidence: 83%
See 2 more Smart Citations
“…1.5°. Although the molecular geometry and, therefore, molecular packing in bay-2Pt-PDI is quite different to that in its previously reported Pd analogue, 84 due to the presence of cis-Pt(PPh 3 ) 2 Br rather than trans-Pd(PPh 3 ) 2 Br groups, there is no PDI−PDI π-stacking in either structure.…”
Section: ■ Expermental Methodscontrasting
confidence: 83%
“…Recently, it was reported that trans -Pd­(PPh 3 ) 2 Cl substituents can be readily incorporated into the meso -positions of polymethines and merocyanines, and Pd­(PPh 3 ) 2 Br into the 1,7-positions of PDIs, through reaction of Pd­(PPh 3 ) 4 with the corresponding halogen derivatives, and that these substituents are effective disaggregating groups that disrupt intermolecular dye–dye π–π interactions. , This reaction was extended to obtain molecules in which Pt­(II) is σ-bonded to a PDI core and molecules bay -Pt-PDI – where, in contrast to its Pd­(II) analogues, the two phosphines are cis to one another–and cyclo -Pt-PDI were obtained . Given the rapid intersystem crossing to the triplet manifold seen for Pt-acetylide-functionalized PDIs, , we were interested in the effect of Pt directly bound to the PDI and so here we study the previously reported examples, bay -Pt-PDI and cyclo -Pt-PDI , in more detail, along with related new compounds ortho -Pt-PDI , ortho -Pd-PDI , and bay -Br/ cyclo -Pt-PDI (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies explore dyes obtained from palladium‐catalyzed cross‐coupling reactions. Crystal structures of Pd‐substituted dyes have been published by Davydenko et al., who demonstrated the suppressive effect of bulky meso ‐substituents on aggregation [16d] …”
Section: Substitution Of Meso‐chloride Substituentsmentioning
confidence: 99%
“…This technique can use small organic molecules to absorb and emit photons in the therapeutic window of 650–1400 nm (depending on the tissue present), where the absorption and autofluorescence of the biological matrix are the lowest, leading to the deepest penetration depth. Higher resolution in this region is desirable and is directly related to increased Stokes shifts (change in energy between absorption and emission curves), high fluorescence quantum yields (ratio of the number of photons emitted to the number of photons absorbed), and absorption as well as emission within the therapeutic window. Materials with these properties could offer new advances in emissive material applications such as biological imaging. One of the most intriguing dyes for imaging applications is based on a donor–acceptor–donor (D–A–D) design with a benzobisthiadiazole acceptor and two triphenylamine donor groups (CH1055-PEG) which emits in the NIR II window (Figure ); however, the fluorescence quantum yield can still be improved (ϕ = 0.3%) . Further understanding of the fundamental photophysical properties of NIR conjugated systems is needed to rationally design future generations of applied materials with tailored emissive properties for numerous applications, including biological imaging.…”
Section: Introductionmentioning
confidence: 99%